ISLAM MODERASI BERAGAMA: METODOLOGI STUDI ISLAM - Eneng Irna Puspa Sari; Ahmad Fadlan; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to provide a comprehensive understanding of a non-extremist religious attitude, covering both right-wing extremism (radical/rigid) and left-wing extremism (liberal/unrestrained), through the concept of religious moderation or wasathiyah in Islam. The diversity of ethnicities, cultures, and religions in Indonesia is a double-edged sword with the potential to trigger horizontal conflicts if religious understanding becomes rigid and exclusive. The phenomenon of polarization due to extremist movements has threatened social cohesion and national integration. Therefore, this study examines the definition of religious moderation as a just and balanced middle path, as well as the implementation of the wasathiyah concept through three main pillars: tawassut (moderation), i'tidal (proportionality), and tasamuh (tolerance). This implementation is applied in three practical domains: moderation in creed (aqidah), worship (ibadah), and morality (akhlaq). By understanding religious moderation, Muslims are expected to embody Islam as rahmatan lil 'alamin (mercy for all creation), maintain harmony, reject violence in the name of religion, and uphold the fundamental principles of creed and sharia within a pluralistic society.